The Evaluation of the Implementation of the Merdeka Curriculum in English Learning at SMPN 20 Kota Bengkulu - Pitriani, Meni (Lembaga Riset dan Inovasi Almatani, 2025)
The Merdeka Curriculum is an educational policy in Indonesia that grants schools autonomy to design and implement curricula based on their conditions, potential, and student needs. This study evaluates its implementation in English learning at SMPN 20 Kota Bengkulu using a descriptive qualitative method with interviews, observations, and document analysis as data collection techniques. The CIPP model (Context, Input, Process, and Product) is used for evaluation. In terms of context, SMPN 20 Kota Bengkulu has developed its Operational School Curriculum (KOSP) in alignment with the Merdeka Curriculum, ensuring flexibility and student-centered learning. The Vice Principal and teachers confirmed that KOSP integrates Pancasila-based character education. Regarding input, the school has improved facilities, teacher competencies, and learning materials. Teachers have received training, although challenges remain in diversifying teaching resources to accommodate students' diverse needs. In the process evaluation, teachers have adopted differentiated instruction and project-based learning, yet managing students' varying abilities remains a challenge. Assessment methods (diagnostic, formative, and summative) are applied effectively but require further refinement. The Pancasila Student Profile Strengthening Project (P5) has positively influenced students' teamwork, responsibility, and social awareness. Overall, the Merdeka Curriculum at SMPN 20 Kota Bengkulu has been progressing well with strong institutional support. However, continuous improvements in teaching strategies, assessment methods, and resource allocation are needed for greater effectiveness.